Internalisasi Nilai-Nilai Multikultural Melalui Budaya Nyama Beraya Pada Masyarakat Muslim Pegayaman - Achmad Fauzi Fauzi (LPPM Institut Pesantren KH. Abdul Chalim, 2019)
Nyama Culture is a culture that encourages people to have tolerance attitudes and behaviors for differences because they see others as their own brothers. The form of Nyama culture in Pegayaman is realized by acculturation of local religious and cultural traditions such as the tradition of crossing or the day of cutting off large religious holiday animals such as Eid al-Fitr, Maulid Nabi, Eid al-Adha and several other big celebrations. Where in every celebration of the big day Muslims continue to preserve their ancestral culture, namely Ngejot or provide various types of food to Nyama Hindu. The discussion of this study is 1) The existence of Nyama Beraya culture is influenced by: historical background, cultural acculturation, community cohesiveness, openness of society, Islamic religious ideology. 2) The process of internalizing multicultural values ​​through the culture of Nyama Beraya in Muslim communities pegayaman through three stages, namely: planting, practice and appreciation. 3) The strategy of internalizing multicultural values ​​through the culture of Nyama Beraya in Muslim communities pegayaman consists of: free strategies, traditional strategies and transinternal strategies. 4) The impact of the internalization of multicultural values ​​through the culture of Nyama Beraya in Muslim communities pegayaman includes: no conflict, high spirit of knitting unity and preventing radicalism, growing togetherness, high enthusiasm of the community to maintain the tradition and the friendly welcome of the community.